Blended Film from PVA and Sansevieria trifasciata Dichloromethane Fraction for Reducing Heat Radiation from Smartphones - Ilmiawati, Auliya; Pujiyati,; Hidayat, Asep; Sugita, Purwantiningsih; Irfana, Luthfan; Arifin, Budi (Makara Journal of Science, 2019)
It has been reported that the lidah mertua plant (Sansevieria trifasciata) can absorb electromagnetic radiation from vari-ous electronic equipment. The current study aimed to make a film layer from polyvinyl alcohol (PVA) and a dichloro-methane (DCM) fraction of S. trifasciatato reduce heat radiation from smartphones. S. trifasciataleaves were macer-ated using ethanol and partitioned with ethyl acetate, DCM, and n-butanol. The DCM fraction was chosen to create the film, for which PVA was also used. The blended film made from PVA and 0.02% DCM reduced heat radiation from smartphones by up to 4.4 °C starting from the first minute of use; its heat reduction remained stable until the 20th mi-nute. Based on these results, it was determined that the active compounds in the DCM fraction are closely related to saponin-type steroids.